Web-based Academic Information System Design at Al-mukhlisin High School Bogor - Prabandari, Sari; Imanuddin Nugraha , Fathan (ASIAN PUBLISHER, 2023)
Academic information system is an application designed for the needs of managing school academic data so that schools can manage academic data better and more efficiently. Website creation in this study uses the programming language PHP Native and JavaScript, for the design used is CSS and the CSS Framework, namely Bootstrap, and the Database Engine used is the MySQL Database. The application that will be made will be able to perform CRUD operations for student data, student grades, teachers, subjects, posts, student and user accounts, besides that the front page will display information about school profiles and activities. Complete CRUD operations can only be performed by the admin, while students can only see their own data (including grades). Forms that will be created include Admin Login Form, Student Login Form, User Registration Form (Admin), Student Account Registration Form, Add Student Data Form, Value Input Form, Create Post Form, Student Data Edit Form, Value Edit Form, Post Edit Form and User Edit Forms. In the development which will later produce a web-based academic information system application, it is hoped that it can further assist Al-Mukhlisin Bogor Islamic High School in terms of managing academic data so that it can be even better and more effective. Students can access and view grades, personal data or information about school activities on the web-based academic application.